Lactation performance of dairy cows fed rehydrated and ensiled corn grain differing in particle size and inclusion in the diet - Castro, Lucas Parreira de (2017)
Rehydration and ensiling of mature ground corn (REC) can increase starch digestibility, especially if fine ground. Kernels from a high vitreous endosperm (84 ± 3 %) were either ground using a 3 (Fine) or 9 (Coarse) mm sieve, resulting in geometric mean particle sizes (GMPS) of 1,591 and 2,185 μm before ensiling. Ground corn was rehydrated to achieve 40 % moisture and ensiled in 200 L galloons for 205 days before beginning experimental period. Composite samples of each gallon (n = 15 per GMPS) were incubated in rumen cannulated lactating dairy cows before and after ensiling. The DM degradation was measured at 0, 3, 6, 18 and 48 hours. Sixteen lactating Holstein dairy cows (152 ± 96 DIM and 35.8 ± 4.4 kg of milk/d) were blocked by parity and milk yield, and randomly assigned to one of four treatments in a 2 x 2 factorial arrangement of treatments with a replicated 4 x 4 latin square design experiment with 14 of adaptation and 7 of data collection. The diets were: 1) high starch and fine REC, 2) high starch and coarse REC, 3) low starch and fine REC, and 4) low starch and coarse REC. High starch diets contained 29.2 and low starch diets contained 23.5 % of starch in DM. The fine ground corn resulted in slower grinding rate (3.9 vs 11.7 ton/h). The REC particle size did not affect DM loss (11.3 % of ensiled), pH (3.8), and N-NH3 (4.7 % of total N). Ensiling of ground corn increased particles per gram (580 vs 890 particles/g), surface area (22.8 vs 23.4 cm2/g), and effective rumen degradation (34.1 vs 63.7 % of DM) regardless particle size. Fine REC tended to result in lower DMI and DOMI than coarse REC only when fed in high starch diets (20.2 vs 20.7 and 12.6 vs 13.8 kg/d, respectively), compared with fine and coarse REC in low starch diets (21.0 vs 20.7 and 13.6 vs 13.3 kg/d, respectively). The starch concentration or REC particle size did not affect milk yield (31.0 kg/d). Fine REC resulted in greater ECM/DOMI than coarse REC only when fed in high starch diets (2.39 vs 2.08) compared with low starch diets (2.17 vs 2.17). Fine REC tended to increase starch digestibility (97.2 vs 96.4 % of intake). In high starch diets, the fine REC increased plasma D-lactate (81.1 vs 60.1 mM) but did not affect in low starch diets. Fine grinding dry corn is slower than coarse grinding and particle size of REC did not affect DM loss. Particle size of REC did not affect milk yield in high or low starch diets and fine REC increased ECM/DOMI when fed in high starch diets.